Long-term effect of aspirin on colorectal cancer incidence and mortality: 20-year follow-up of five randomised trials. - Rothwell, P; Wilson, M; Elwin, C; Norrving, B; Algra, A; Warlow, C; Meade, T (2010)
BACKGROUND: High-dose aspirin (≥500 mg daily) reduces long-term incidence of colorectal cancer, but adverse effects might limit its potential for long-term prevention. The long-term effectiveness of lower doses (75-300 mg daily) is unknown. We assessed the effects of aspirin on incidence and mortality due to colorectal cancer in relation to dose, duration of treatment, and site of tumour. METHODS: We followed up four randomised trials of aspirin versus control in primary (Thrombosis Prevention Trial, British Doctors Aspirin Trial) and secondary (Swedish Aspirin Low Dose Trial, UK-TIA Aspirin Trial) prevention of vascular events and one trial of different doses of aspirin (Dutch TIA Aspirin Trial) and established the effect of aspirin on risk of colorectal cancer over 20 years during and after the trials by analysis of pooled individual patient data. RESULTS: In the four trials of aspirin versus control (mean duration of scheduled treatment 6·0 years), 391 (2·8%) of 14 033 patients had colorectal cancer during a median follow-up of 18·3 years. Allocation to aspirin reduced the 20-year risk of colon cancer (incidence hazard ratio [HR] 0·76, 0·60-0·96, p=0·02; mortality HR 0·65, 0·48-0·88, p=0·005), but not rectal cancer (0·90, 0·63-1·30, p=0·58; 0·80, 0·50-1·28, p=0·35). Where subsite data were available, aspirin reduced risk of cancer of the proximal colon (0·45, 0·28-0·74, p=0·001; 0·34, 0·18-0·66, p=0·001), but not the distal colon (1·10, 0·73-1·64, p=0·66; 1·21, 0·66-2·24, p=0·54; for incidence difference p=0·04, for mortality difference p=0·01). However, benefit increased with scheduled duration of treatment, such that allocation to aspirin of 5 years or longer reduced risk of proximal colon cancer by about 70% (0·35, 0·20-0·63; 0·24, 0·11-0·52; both p<0·0001) and also reduced risk of rectal cancer (0·58, 0·36-0·92, p=0·02; 0·47, 0·26-0·87, p=0·01). There was no increase in benefit at doses of aspirin greater than 75 mg daily, with an absolute reduction of 1·76% (0·61-2·91; p=0·001) in 20-year risk of any fatal colorectal cancer after 5-years scheduled treatment with 75-300 mg daily. However, risk of fatal colorectal cancer was higher on 30 mg versus 283 mg daily on long-term follow-up of the Dutch TIA trial (odds ratio 2·02, 0·70-6·05, p=0·15). INTERPRETATION: Aspirin taken for several years at doses of at least 75 mg daily reduced long-term incidence and mortality due to colorectal cancer. Benefit was greatest for cancers of the proximal colon, which are not otherwise prevented effectively by screening with sigmoidoscopy or colonoscopy. FUNDING: None.